Ictal Intracranial Recording from a ‘Burned-Out Hippocampus’ - Gatzonis, Stylianos (Med Princ Pract, 2012)
OBJECTIVE: To present a case involving a discrepancy in the presurgical data of a patient suffering from pharmacoresistant mesial temporal lobe epilepsy. CLINICAL PRESENTATION AND INTERVENTION: A 47-year-old, female patient with complex partial seizures since her twenties came to be evaluated in the Epilepsy Surgery Unit. The ictal electroencephalogram suggested a left temporal epileptogenic zone and the magnetic resonance image showed an abnormality in the right mesial temporal lobe. Intracranial monitoring revealed a pacemaker zone in the right hippocampus that discharged fast spreading to the left mesial temporal lobe, a phenomenon known as ‘burned-out hippocampus’. CONCLUSION: The intracranial recording, even though it is an invasive procedure, was necessary for the presurgical evaluation of our patient. This case demonstrates the risks of using surface electroencephalography to determine localization of epileptogenic zones.